2017
DOI: 10.1038/srep46080
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of small RNAs during endoplasmic reticulum stress

Abstract: The accumulation of misfolded proteins in the endoplasmic reticulum (ER) lumen due to the disruption of the homeostatic system of the ER leads to the induction of the ER stress response. Cellular stress-induced pathways globally transform genes expression on both the transcriptional and post-transcriptional levels with small RNA involvement as regulators of the stress response. The modulation of small RNA processing might represent an additional layer of a complex stress response program. However, it is poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 90 publications
2
12
0
Order By: Relevance
“…Although our studies were similar to a previous report on Jurkat pre-T- cells that did not examine piRNAs 46 , we found a decrease in the relative quantity of miRNA-mapped reads and also noted a large relative increase in piRNA-mapped reads (3–4 fold) that were most significantly induced during the cell fate decision stage (6 hours). Furthermore, different mechanisms of ER stress induction had very similar effects on piRNA expression profiles, and resulted mainly in induction of these RNAs, whereas the total miRNAs were reduced.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although our studies were similar to a previous report on Jurkat pre-T- cells that did not examine piRNAs 46 , we found a decrease in the relative quantity of miRNA-mapped reads and also noted a large relative increase in piRNA-mapped reads (3–4 fold) that were most significantly induced during the cell fate decision stage (6 hours). Furthermore, different mechanisms of ER stress induction had very similar effects on piRNA expression profiles, and resulted mainly in induction of these RNAs, whereas the total miRNAs were reduced.…”
Section: Discussionsupporting
confidence: 89%
“…Despite these important discoveries, the majority of research has been performed in cancer cell lines. Recently, a class of small non-coding RNAs, miRNA, has been linked to the unfolded protein response pathway, and shown that these miRNAs through their posttranscriptional effects on multiple components of UPR can determine cell fate during ER stress 45 , 46 (reviewed in 7 , 47 , 48 ). Although this miRNA’s role in UPR remains extensively studied, the functions of other small non-coding RNA classes in this pathway remain relatively unknown 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A particular pharmacological interest relies on the design of tailored enzymes with specific RNA cleavage targets (Tamkovich et al, 2016). Recent work on RNases’ action within a cellular environment is helping to unravel their natural in vivo substrates (Honda et al, 2015; Lyons et al, 2017; Mesitov et al, 2017). A proper knowledge of the RNases’ active site architecture should lead to the design of specific inhibitors of their biological functions (Chatzileontiadou et al, 2015; Chatzileontiadou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…5–7 Its protein maturation machinery and other energy-intensive processes make the ER highly sensitive to numerous factors, including toxins, nutrition, and energy deprivation, redox imbalances, and disorder in Ca 2+ storage. 8 …”
Section: Introductionmentioning
confidence: 99%